2009
DOI: 10.1007/s00425-009-1081-5
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterisation of the intergeneric hybrids between Dendranthema morifolium and Artemisia vulgaris exhibiting enhanced resistance to chrysanthemum aphid (Macrosiphoniella sanbourni)

Abstract: Aphids represent the most destructive of chrysanthemum pests to cultivation. Reliable variety sources of resistance and control methods are limited, so development of highly resistant breeding lines is desirable. An intergeneric hybrid between Dendranthema morifolium (chrysanthemum) variety 'Zhongshanjingui' and Artemisia vulgaris (mugwort) 'Variegata' was attempted. Most of the hybrid embryos aborted at an early developmental stage. Embryo rescue allowed the generation of hybrid plants, whose hybridity was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 27 publications
0
52
1
1
Order By: Relevance
“…The aphid infestation protocol followed the method of Deng et al (2010). Briefly, five 2nd instar aphids were carefully placed on each stem tip of the test plants with a soft brush.…”
Section: Sa and Aphid Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The aphid infestation protocol followed the method of Deng et al (2010). Briefly, five 2nd instar aphids were carefully placed on each stem tip of the test plants with a soft brush.…”
Section: Sa and Aphid Treatmentsmentioning
confidence: 99%
“…Artemisia vulgaris (AV) 'Variegata' (mugwort) is an aphid-resistant species due to its leaf morphology and bioactive essential oil content (Deng et al, 2010). Macrosiphoniella sanbourni is a major pest of chrysanthemums, and reduces vegetative growth and flower production and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, several studies have shown the cross compatibility between cultivated chrysanthemums and species of Chrysanthemum and related genera (Fukai et al, 2000;Sun et al, 2010b), Thus far, potentially useful F 1 hybrids between cultivated chrysanthemums and species of Chrysanthemum and related genera have been produced through inter-specific or inter-generic hybridization with embryo rescue (Watanabe, 1977;Furuta et al, 2004). Recently, Deng et al (2010Deng et al ( , 2012) transferred resistance to aphid and Alternaria leaf spot from Artemisia vulgaris to cultivated chrysanthemums, and the same authors obtained some F 1 hybrids with enhanced cold tolerance through the hybridization of cultivated chrysanthemum and Ajania przewalskii . Some ornamentally important traits, as well as traits of heat and drought tolerance, were also transferred to chrysanthemum by other authors (Zhao et al, 2007;Sun et al, 2010a;Cheng et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some of the species are endowed with novel traits of horticultural interest and strong stress and disease resistance that are not present in chrysanthemum cultivars (Sun et al, 2010a;Deng et al, 2010Deng et al, , 2011Deng et al, , 2012. Hence, many new cultivars of chrysanthemum with improved target traits possibly will emerge once hybrid parents are expanded to wild species of Chrysanthemum and related genera.…”
Section: Introductionmentioning
confidence: 99%
“…They may have gene fl ow bridge by introgressive hybridization between the Chrysanthemum fruticulosum complex and Artemisia obtusiloba. Artemisia can be artifi cially hybridized with Chrysanthemum such as Dendranthema (=Chrysanthemum) morifolium X Artemisia vulgaris by Deng et al (2010). …”
mentioning
confidence: 99%